(untitled) (Journal of Mathematics Mechanics and Computer Science, 2012)
In this paper one of correct ε -approximation of the system of equations of heat convection for the Kelvin-Voight fluids is investigated. The existence and uniqueness of a strong solution of ε– regularized problem and it is convergence to the strong solution of the initial problem as ε 7→ 0 are proofed. The estimates for the rate of convergence of solution are obtained.